Abnormal serum free light chain ratio predicts poor overall survival in mantle cell lymphoma. (24th October 2012) - Furtado, Michelle; Shah, Nimish; Levoguer, Alison; Harding, Stephen; Rule, Simon
Summary Serum free light Chain (sFLC) ratios have been correlated with survival outcomes in Hodgkin and non‐Hodgkin lymphoma subtypes. This study was undertaken to investigate the prognostic impact of abnormal sFLC ratios in mantle cell lymphoma (MCL). two patient cohorts were analysed for sFLC parameters: a preliminary retrospective cohort and a uniformly treated cohort of 20 relapsed/refractory MCL patients, enrolled in a phase II clinical trial of single agent lenalidomide treatment. 52% of patients had an abnormality of one or more sFLC parameter (71% of the first cohort and 40% of the second cohort). In cohort two, a high baseline SFLC ratio correlated with poorer overall survival (OS) compared to a low/normal ratio (median OS: 1·4 months vs. 19 months respectively; P = 0·001). For patients presenting with an elevated sFLC ratio at trial entry a rise of >35% in the sFLC ratio correlated with disease progression and a sFLC ratio of >2× normal at trial entry correlated with aggressive disease. These data are the first to show a clear clinical correlation between sFLC ratios and survival outcomes in a uniformly treated cohort of MCL patients. We suggest that these markers may be useful in managing patients with MCL in the future.